CHORAL PROJECTIONS AND EMBOLIMA IN EURIPIDES' TRAGEDIES*. (25th March 2015) - Unknown
Abstract : In his Poetics Aristotle argued that the chorus being one of the actors, as in Sophocles, was its finest function, while he criticized Euripides' choruses for not being part of the whole and not sharing in the action. Aristotle also mentioned that in the work of other tragic poets (probably from the late fifth century onwards) the chorus's odes stood outside the context of the dramatic myth, and named these odes embolima, ascribing their origin to Agathon (who was active in the last quarter of the fifth centurybc ). So we should not assume that in Aristotle's view Euripides was responsible for paving the way for the practice of the embolima . However, it is at least certain that, in his opinion, Euripides' choral odes were less dependent upon the dramatic plot than those of Sophocles.